Prognostic impact of distinct genetic entities in pediatric diffuse glioma WHO‐grade II—Report from the German/Swiss SIOP‐LGG 2004 cohort. Issue 8 (1st May 2020) - Falkenstein, Fabian; Gessi, Marco; Kandels, Daniela; Ng, Ho‐Keung; Schmidt, René; Warmuth‐Metz, Monika; Bison, Brigitte; Krauss, Juergen; Kortmann, Rolf‐Dieter; Timmermann, Beate; Thomale, Ulrich‐Wilhelm; Albert, Michael H.; et al.
Abstract: Reports on pediatric low‐grade diffuse glioma WHO‐grade II (DG2) suggest an impaired survival rate, but lack conclusive results for genetically defined DG2‐entities. We analyzed the natural history, treatment and prognosis of DG2 and investigated which genetically defined sub‐entities proved unfavorable for survival. Within the prospectively registered, population‐based German/Swiss SIOP‐LGG 2004 cohort 100 patients (age 0.8‐17.8 years, 4% neurofibromatosis [NF1]) were diagnosed with a DG2. Following biopsy (41%) or variable extent of resection (59%), 65 patients received no adjuvant treatment. Radiologic progression or severe neurologic symptoms prompted chemotherapy (n = 18) or radiotherapy (n = 17). Multiple lines of salvage treatment were necessary for 19/35 patients. Five years event‐free survival dropped to 0.44, while 5 years overall survival was 0.90 (median observation time 8.3 years). Extensive genetic profiling of 65/100 DG2 identified Histone3‐K27M ‐mutation in 4, IDH1 ‐mutation in 11, BRAF‐V600 ‐mutation in 12, KIAA1549‐BRAF ‐fusions in 6 patients, while the remaining 32 tumor tissues did not show alterations of these genes. Progression to malignant glioma occurred in 12 cases of all genetically defined subgroups within a range of 0.5 to 10.8 years, except for tumors carrying KIAA1549‐BRAF ‐fusions. Histone3‐K27M ‐mutant tumors proved uniformly fatal within 0.6 to 2.4 years. The current LGG treatment strategy seems appropriate for all DG2‐entities, with the exemption of Histone3‐K27M ‐mutant tumors that require a HGG‐related treatment strategy. Our data confirm the importance to genetically define pediatric low‐grade diffuse gliomas for proper treatment decisions and risk assessment. Abstract : What's new? Pediatric low‐grade diffuse gliomas histologically resemble their adult counterparts, but they differ greatly in terms of genetics, clinical behavior, and prognosis. Here, the authors investigated genetic mutations in 65 pediatric grade 2 diffuse gliomas (DG2), looking for a correlation with long‐term outcome. All 4 tumors carrying the K27M mutation in the Histone3 gene were fatal. Conversely, none of the 6 tumors carrying a particular duplication of the BRAF gene, called the KIAA1549‐BRAF fusion, progressed to malignant glioma. The authors characterized the tumor genetics with respect to prognosis, age at onset, and response to treatment.